2017
DOI: 10.1007/s41207-017-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of OFMSW co-digestion with sewage sludge for increasing biogas production at wastewater treatment plants

Abstract: Sweden has the ambition to increase its annual biogas production from the current level of 1.9 to 15 TWh by 2030. The unused capacity of existing anaerobic digesters at wastewater treatment plants is among the options to accomplish this goal. This study investigated the feasibility of utilizing the organic fraction of municipal solid waste (OFMSW) as a co-substrate, with primary and waste-activated sewage sludge (PWASS) for production of biogas, corresponding to 3:1 ratio on volatile solid (VS) basis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For example, Mattioli et al (2017) took the co-digestion technology of a sewage plant in Rovereto, Italy, as a case example; the results showed that the organic loading rate (OLR) could be doubled without any process difficulties, and the increased biogas yield could satisfy 85% of the plant’s energy demand. Similar conclusions have also been drawn by Björn et al (2017) , who proved that co-digestion with food waste has the potential to increase biogas production by approximately four times. Similar techno-economic studies can also be found in Glivin et al (2018 , 2019b ), Lamidi et al, 2019 and Walekhwa et al (2014) .…”
Section: Literature Reviewsupporting
confidence: 84%
“…For example, Mattioli et al (2017) took the co-digestion technology of a sewage plant in Rovereto, Italy, as a case example; the results showed that the organic loading rate (OLR) could be doubled without any process difficulties, and the increased biogas yield could satisfy 85% of the plant’s energy demand. Similar conclusions have also been drawn by Björn et al (2017) , who proved that co-digestion with food waste has the potential to increase biogas production by approximately four times. Similar techno-economic studies can also be found in Glivin et al (2018 , 2019b ), Lamidi et al, 2019 and Walekhwa et al (2014) .…”
Section: Literature Reviewsupporting
confidence: 84%
“…The share of co-substrate in the feedstock was maintained at the level from 6.2 to 21.2% and it depended on the amount of sewage sludge (Figure 8). The dosing of co-substrate should be constantly controlled due to the possibility of biogas composition deterioration (increase the CO 2 content) and operational problems, especially during the dewatering of digested sludge [55,75]. It is assumed that the share of additional substrates for co-digestion with sewage sludge should not exceed 30% [76].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to use the energy-rich methane in a combined heat and power (CHP) unit for electricity and heat production quickly allowed the transition of AD from a waste treatment technology to an integrated system for renewable energy recovery. Different organic waste streams, such as animal manure (Holm- Nielsen et al 2009), waste activated sludge (Appels et al 2008), the organic fraction of municipal solid waste (Hartmann and Ahring 2006) have been valorised through AD, either as such or through co-digestion with other waste streams (Björn et al 2017, Mata-Alvarez et al 2011). In the framework of the current transition from "wasteto-energy" to "waste-to-resource", the recovery of nutrients, in addition to energy, has become more and more pressing to (1) safeguard natural resources and (2) ensure long-term economic viability of the AD process.…”
Section: Introductionmentioning
confidence: 99%